2013
DOI: 10.4236/ijmpcero.2013.24015
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Impact of Inter-Fraction Variation in Interstitial HDR Brachytherapy

Abstract: Background: Patient setup errors in External Beam Radiotherapy (EBRT) are minimized to a great extent, due to recent technological developments, but in contrary brachytherapy received less attention in inter-fraction catheter movement and its impact in dose delivery. This article deals with inter-fraction interstitial catheter movement and its impact in dose delivery to the target. An attempt is made to study the dosimetric impact of this variation. Objectives: The objective of the study is to evaluate the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Kandasamy et al [14] con-cluded that repeat-CT on the fifth day from the application is sufficient. CT/MRI imaging before each fraction can be an effective way to find the tumor shrinkage, edema and applicator displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Kandasamy et al [14] con-cluded that repeat-CT on the fifth day from the application is sufficient. CT/MRI imaging before each fraction can be an effective way to find the tumor shrinkage, edema and applicator displacement.…”
Section: Discussionmentioning
confidence: 99%
“…In our study for flexible catheter based interstitial Brachytherapy, the planning CT scan was done 1 or 2 days after the implant. This had the beneficial effect of reduced tissue edema and hence a reduction in the effect of Kandasamy et al [14] observed inter-fraction errors frequently in the interstitial implants and recommended imaging before each fraction and re-planning based on that. In-vivo dosimetry with microMOSFET can be alternative for pre-treatment CT method with the added advantage of instant verification, convenient to patient, save the quality time of man power and no additional exposure unlike the multiple CT.…”
Section: Discussionmentioning
confidence: 99%
“…This method drastically cut down the D90 of CTV within ±5% in contrast with their earlier study of 35% to 40%. Kandasamy et al [14] suggested piece of micropore paper pasted on each applicator can minimize the displacement significantly. We also used the same method to arrest the applicator movement at certain extent.…”
Section: Discussionmentioning
confidence: 99%